DESIGN OF AKKALKARA (SPILANTHES ACMELLA) FORMULATIONS FOR ANTI-MICROBIAL AND TOPICAL ANTI-INFLAMMATORY ACTIVITIES - NITIN GUPTA; ANKIT R. PATEL; RAVINDRA R. P (International Journal of Pharma and Bio Sciences, 2012)
For centuries, Spilanthes acmella (L.) Murr. (Fam. Compositae) has been recommended in traditional medicine for treatment of toothache, rheumatism and fever. Of the reported phytoconstituents of the plant, Spilanthol is known to possess antibacterial and anti inflammatory activity. The aim of the current investigation is to evaluate the potential of novel vesicular carrier, ethosomes, containing the methanolic extract of Spilanthes acmella, for anti inflammatory action via transdermal route and to test the potential of the herbal extract for antimicrobial property when formulated as an oral mucoadhesive gel. Drug loaded ethosomes prepared using phospholipid and ethanol, were optimized and characterized for entrapment efficiency, vesicular size, shape, in vitro skin permeation, and stability. The ethosomal vesicles were incorporated in carbopol gel base and its antiâ€inflammatory efficiency was compared with the marketed diclofenac gel. Mucoadhesive oral gels containing extract were formulated using different concentrations of polymers and extracts and tested for parameters like viscosity and mucoadhesive behavior. The optimized formulation was evaluated for antimicrobial activity against different microorganisms responsible for causing tooth decay using well diffusion method. The results fully validate the claims of the traditional medicine about the use of Akkalkara for local anti-inflammatory and anti-microbial properties and confirm the suitability of ethosomes for transdermal delivery of active constituents of this herbal formulation. Both formulations show results comparable to that of standard allopathic formulations.